CURRENT STATE OF THE PROBLEM AND WAYS OF IMPROVING CHARACTERISTICS OF WORKING PROCESS OF COMBUSTION CHAMBERS OF LOW-DIMENSIONAL GTE - A. M. Lansky; S. V. Lukachev; S. G. Matveev (Научный вестник МГТУ ГА, 2016)
The condition of research in the field of the organization of working process in chambers of combustion of low-dimensional GTE is considered. Ways of improving characteristics of combustion chambers are planned.